2018
DOI: 10.30799/jnst.169.18040523
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activity of Hydrophila auriculata Leaves Extract and Silver Nanoparticles

Abstract: Antioxidant activity of Hydrophila auriculata leaf extract and silver nanoparticles (AgNPs) were carried out for proving its utility in free radical mediated diseases. The flower extract and silver nanoparticles were screened for in vitro antioxidant activity by oxygen radical scavenging such as DPPH, total antioxidant assay and superoxide radical scavenging activity at different concentrations. The antioxidant potential was found to be dose dependent. AgNPs possess probable antioxidant activity as compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…According to Mohan et al (2014), biosynthesised AgNPs from Canthium coromandelicum leaves extract exhibited higher free radical scavenging activity compared to leaves extract and this clearly shows that synthesised AgNPs using plant material have higher antioxidant property compared to the crude extracts [36]. The present result is in accordance with previous report [37]. Previous study reported that Tualang honey contains high level of ascorbic acid content (36.09±0.41 mg/100 g of honey) [18].…”
Section: Resultssupporting
confidence: 91%
“…According to Mohan et al (2014), biosynthesised AgNPs from Canthium coromandelicum leaves extract exhibited higher free radical scavenging activity compared to leaves extract and this clearly shows that synthesised AgNPs using plant material have higher antioxidant property compared to the crude extracts [36]. The present result is in accordance with previous report [37]. Previous study reported that Tualang honey contains high level of ascorbic acid content (36.09±0.41 mg/100 g of honey) [18].…”
Section: Resultssupporting
confidence: 91%
“…All extracts showed the highest reduction capacity (optical density) as compared with ascorbic acid at a tested amount of 1000 μg/mL. This capacity of the extracts to reduce Fe 3+ could be ascribed to the presence of reduction agents, such as polyphenols, and the number and/or the position of the hydroxyl groups on polyphenols [45].…”
Section: Discussionmentioning
confidence: 89%
“…The reducing power of compounds would serve as an indicator of their antioxidant potential. Thus, in the current research, we assessed the reducing power of the extracts by measuring their capacity to reduce Fe 3+ to Fe 2+ by donating electron [45]. All extracts showed the highest reduction capacity (optical density) as compared with ascorbic acid at a tested amount of 1000 μg/mL.…”
Section: Discussionmentioning
confidence: 99%